Degradable environment-friendly electric insulation plastic packaging bag and preparation method thereof

By adding raw materials such as zirconium organophosphate, hydrophobically modified cellulose nanocrystals and polyimide/aluminum fluoride composite nanofibers to the polylactic acid packaging bag, the problem of insufficient insulation performance of polylactic acid at high temperatures is solved, and the heat resistance and insulation performance of the packaging bag at high temperatures is improved, while maintaining the degradability of the material.

CN119708787AActive Publication Date: 2025-03-28QINGDAO ZHOUSHI PLASTIC PACKAGE

Patent Information

Application Number
CN202411753639.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-28
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

The insulating performance of polylactic acid at high temperatures is insufficient, resulting in thermal deformation and reduced electrical insulation of packaging bags under high temperature environments.

Method used

Polylactic acid is used as the substrate and raw materials such as zirconium organophosphate, hydrophobically modified cellulose nanocrystals and polyimide/aluminum fluoride composite nanofibers are incorporated. Through the interaction and combination of these materials, the heat resistance and electrical insulation properties of polylactic acid are improved.

Benefits of technology

It improves the heat resistance and insulation performance of packaging bags at high temperatures, enhances its tensile strength and electrical insulation capabilities, and maintains the degradability of the material, meeting environmental protection requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the field of packaging materials, and particularly discloses a degradable environment-friendly electric insulation plastic packaging bag and a preparation method thereof. The degradable environment-friendly electric insulation plastic packaging bag is prepared from the following raw materials in parts by weight: 100 parts of polylactic acid, 1-4 parts of organic zirconium phosphate, 2-5 parts of hydrophobic modified cellulose nanocrystals, 4-10 parts of polyimide / aluminum fluoride composite nanofibers, 1-3 parts of a dispersing agent, 1-4 parts of an antioxidant, 3-5 parts of inorganic filler, 1-3 parts of a slipping agent, 1-3 parts of an antistatic agent and 3-5 parts of a flame retardant. The packaging bag can be used for objects with high requirements for electrical insulation, has high electrical insulation capacity at high temperature, and is high in transparency and mechanical property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of packaging materials, and more specifically, to a degradable and environment-friendly electrical insulating plastic packaging bag and a preparation method thereof. Background Art

[0002] Electrically insulating packaging bags are mainly used to package items that require electrical insulation performance. These items usually include electrical components, electronic devices and sensitive electronic devices, such as integrated circuits, transistors, resistors, transformers, capacitors, motors, hard disk drives, motherboards, etc. These items need to avoid current leakage or static interference during operation or storage. Electrically insulating packaging bags are usually made of materials with good electrical insulation properties, such as polyethylene, polypropylene, polystyrene, polyphenylene sulfide and other polymer materials. These materials can prevent the flow of charge under the action of an electric field, so they have excellent electrical insulation properties.

[0003] However, these polymer insulating materials cannot be naturally degraded after being scrapped and can only be disposed of by landfill or incineration. Landfill will pollute the soil, and incineration will produce harmful gases, polluting the air and the natural environment. Polylactic acid can be completely decomposed into carbon dioxide and water under the action of enzymes secreted by microorganisms in nature. It is pollution-free to the environment and is one of the most promising biodegradable polymers. Polylactic acid has electrical insulation properties and has been used in electronic product packaging, but the heat deformation temperature of polylactic acid is relatively low, generally around 55°C (non-crystalline state). In high temperature environments, polylactic acid may undergo thermal deformation, resulting in changes in the material structure. In addition, under high temperature conditions, the movement and polymerization of polar functional groups such as ester groups on the polylactic acid molecular chain may lead to weakened interactions between molecular chains, making it easier to form conductive channels or leakage currents, affecting the insulation of packaging bags. In response to the above-mentioned related technologies, the inventors found that the insulation performance of polylactic acid at high temperatures needs to be improved. Summary of the invention

[0004] In order to increase the electrical insulation of a polylactic acid packaging bag at high temperatures, the present application provides a degradable and environmentally friendly electrically insulating plastic packaging bag and a preparation method thereof.

[0005] In the first aspect, the present application provides a degradable and environmentally friendly electrically insulating plastic packaging bag, adopting the following technical scheme: a degradable and environmentally friendly electrically insulating plastic packaging bag, comprising the following raw materials in parts by weight: 100 parts of polylactic acid, 1-4 parts of organic zirconium phosphate, 2-5 parts of hydrophobically modified cellulose nanocrystals, 4-10 parts of polyimide / aluminum fluoride composite nanofibers, 1-3 parts of dispersant, 1-4 parts of antioxidant, 3-5 parts of inorganic filler, 1-3 parts of lubricant, 1-3 parts of antistatic agent, and 3-5 parts of flame retardant.

[0006] By adopting the above technical scheme, biodegradable polylactic acid is used as the substrate, and a small amount of organic zirconium phosphate and hydrophobically modified cellulose nanocrystals are added, and polyimide / aluminum fluoride composite nanofibers are used to modify the polylactic acid-based packaging bag to be heat-resistant. The organic zirconium phosphate plays a heterogeneous nucleation role in the polylactic acid matrix, and the thermal stability of its layered structure can improve the heat resistance and toughness of polylactic acid. In addition, its lamellar structure provides a large number of nucleation sites for polylactic acid, promotes the crystallization of polylactic acid, and the polylactic acid molecular chains are orderly arranged around the nucleation sites to form a more complete crystal structure. In addition, the number of nucleation sites increases, the crystallization rate of polylactic acid increases, the crystallization time is shortened, and a higher degree of crystallinity is achieved more quickly, thereby improving the quality of the polylactic acid. The layered structure of organic zirconium phosphate forms a thermal barrier in the polylactic acid matrix to block the rapid transfer of heat. When polylactic acid is heated, these layered structures can attract and disperse heat, thereby delaying the thermal decomposition process. Through the interaction with polylactic acid, organic zirconium phosphate can change the molecular arrangement and stacking mode of polylactic acid, so that the glass transition temperature of polylactic acid is increased, thereby enhancing its heat resistance. Organic zirconium phosphate can also enhance the mechanical properties of polylactic acid, such as tensile strength and impact strength, so that polylactic acid has good mechanical properties while maintaining high heat resistance. In addition, organic zirconium phosphate will not change the chemical structure of polylactic acid, so that polylactic acid still maintains its original degradability, which meets environmental protection requirements.

[0007] Cellulose nanocrystal is a kind of biodegradable nanofiller, but due to the presence of a large number of hydrophilic hydroxyl groups on its surface, it has poor compatibility with the hydrophobic polylactic acid matrix, making it easy to agglomerate in the polylactic acid matrix and difficult to disperse evenly. Therefore, it needs to be hydrophobically modified. The dispersibility and compatibility of hydrophobically modified cellulose nanocrystals in polylactic acid are improved, and it has good interface bonding with polylactic acid, promotes the directional arrangement and crystallization of polylactic acid molecular chains, inhibits the crystal growth of polylactic acid molecules, reduces the scattering of materials, improves the transparency of materials, and can fill microscopic defects in polylactic acid, effectively inhibit the expansion of cracks, and improve the toughness and elongation at break of materials, so that polylactic acid has high heat resistance and good mechanical properties while maintaining high transparency. In addition, the hydrophobically modified cellulose nanocrystals are evenly dispersed in polylactic acid, and can form a dense network structure in the polylactic acid encapsulation, providing a barrier effect for polylactic acid, and improving the electrical insulation of polylactic acid to a certain extent.

[0008] Aromatic polyimide has excellent mechanical properties, thermal stability and excellent dielectric properties. Aluminum fluoride also has strong electrical insulation. Its fluorine-containing properties can also improve the hydrophobicity of the surface of the composite nanofibers, thereby enhancing the dispersibility of the composite nanofibers in polylactic acid, improving the interfacial effect between the two, and enhancing the heat resistance, mechanical strength and electrical insulation capacity of the packaging bag.

[0009] Optionally, the hydrophobically modified cellulose nanocrystals include cellulose nanocrystals, tannic acid and octadecylamine in a mass ratio of 1:0.4-0.6:0.9-1.

[0010] By adopting the above technical scheme, tannic acid can be oxidized and self-polymerized on cellulose nanocrystals to form a thin layer of polytannic acid, which adheres to the surface of cellulose nanocrystals and shields the hydroxyl groups. Then tannic acid and octadecylamine undergo Michael addition reaction. Since octadecylamine has a higher thermal decomposition temperature, the thermal stability and hydrophobicity of cellulose nanocrystals are improved, so that the cellulose nanocrystals are well dispersed in the polylactic acid matrix, providing more nucleation sites, so that the polylactic acid completes the crystallization process faster, significantly improving the mechanical properties of the packaging bag, enhancing the tensile strength and elongation at break, and the improvement in the dispersion of cellulose nanocrystals makes the grain size smaller and the light transmittance improved.

[0011] Optionally, the preparation method of the hydrophobically modified cellulose nanocrystals is as follows: The pH of the cellulose nanocrystal suspension with a concentration of 2-3 wt% is adjusted to 8-9, Tris buffer and tannic acid are added, and stirred for 20-24 hours to obtain an aqueous dispersion; The anhydrous ethanol solution of octadecylamine is mixed with the aqueous dispersion, stirred at 50-60° C. for 20-24 hours, centrifuged, the precipitate is collected, washed, and freeze-dried to obtain a pretreated cellulose nanocrystal powder; The pretreated cellulose nanocrystal powder is dispersed in deionized water, ultrasonically dispersed for 2-3 hours, 3-aminopropyltrihydroxysilane modified boron nitride nanosheets are added, stirred for 6-8 hours, vacuum filtered, dried at 100-130°C, and ground. The mass ratio of 3-aminopropyltrihydroxysilane modified boron nitride nanosheets to pretreated cellulose nanocrystal powder is 0.1-0.2:1.

[0012] By adopting the above technical scheme, tannic acid is used to form a polytannic acid layer on the surface of cellulose nanocrystals, which is then reacted with octadecylamine to improve the heat resistance of cellulose nanocrystals. Then, boron nitride nanosheets are used for further modification. Boron nitride nanosheets themselves have good thermal stability and can improve the high temperature resistance of cellulose nanocrystals. In addition to the Michael addition reaction with octadecylamine, tannic acid also provides negative charges, thereby electrostatically combining with the positively charged boron nitride nanosheets. Therefore, 3-aminopropyltrihydroxysilane-modified boron nitride nanosheets can combine with pretreated cellulose nanocrystals, thereby improving the strength of cellulose nanocrystals and improving the nitrogen The dispersibility of boron nitride nanosheets reduces agglomeration and condensation, and increases the possibility of forming a thermal conductive network. During the stretching process of the packaging bag, it is more difficult for boron nitride to slide out along the stretching direction, which helps to improve the mechanical strength. The pretreated cellulose nanocrystal powder loaded with boron nitride nanosheets, the two-dimensional structure and high insulation strength of boron nitride nanosheets can prevent the penetration of cellulose nanocrystals under strong electric fields. When it combines with cellulose nanocrystals, the boron nitride nanosheets fill the gaps between the molecular chains and form hydrogen bonds with the cellulose nanocrystals. The structure of the entire system is more tightly combined, reducing the free volume, effectively weakening the movement of the molecular chains, and improving the insulation properties of the composite material.

[0013] Optionally, the organophosphate zirconium is pretreated as follows: the organophosphate zirconium is blended with poloxamer 407 and polycaprolactone in a mass ratio of 0.03-0.05:0.02-0.04:1, followed by granulation.

[0014] By adopting the above technical scheme, the organic zirconium phosphate pretreated with poloxamer 407 and polycaprolactone can further improve the heat resistance and mechanical strength of polylactic acid. The addition of poloxamer 407 increases the mobility of polylactic acid molecular chains and promotes the nucleation and crystallization of polylactic acid. Moreover, the melting point of poloxamer 407 is lower than that of polylactic acid, and it is in a liquefied state before polylactic acid is hot-melted. It has the same α-methyl di-isocyanate as the polylactic acid chain segment and has a similar miscibility, thereby facilitating the local movement of the polylactic acid molecular chain, and thereby causing the polylactic acid chain segments with orientation or incomplete crystallization to recrystallize during the heating process, making the polylactic acid crystal more complete and dense. Polycaprolactone has good compatibility with polylactic acid and can form a blending system with adjustable degradation rate. Moreover, it itself has certain electrical insulation properties, which can optimize the electrical insulation capacity of the packaging bag and improve the heat resistance of polylactic acid.

[0015] Optionally, the polyimide / aluminum fluoride composite nanofibers are prepared by electrospinning a polyamic acid solution and an aluminum fluoride composite followed by imidization, and the mass ratio of the polyamic acid solution to the aluminum fluoride is 1:0.01-0.012.

[0016] By adopting the above technical scheme, polyamic acid is electrospun to obtain a polyamic acid nanofiber matrix. During the thermal imidization process, the amide bond is broken to generate anhydride and amine, and the Al-F bond in aluminum fluoride reacts with the amino group NH2, combines in a covalent bond manner, and adheres to the surface of the polyimide nanofiber. After thermal imidization, the fluorine element is lost in the form of gas during the reaction, so that the fluorine content is reduced, which increases environmental safety, and due to the generation of a cross-linked structure, the tensile properties are enhanced. At the same time, the good dispersibility of aluminum fluoride in polyimide and the interface interaction between the two enhance the mechanical properties of the composite nanofiber. Aluminum fluoride can also hinder the movement of chain segments and reduce the thermal decomposition rate of the composite nanofiber. Both polyimide and aluminum fluoride have strong electrical insulation capabilities, which can improve the heat resistance of polylactic acid while increasing the electrical insulation capability.

[0017] Optionally, the inorganic filler is porous silica.

[0018] By adopting the above technical solution, porous silica as a filler can improve the crystallization rate of polylactic acid, thereby improving the heat resistance of polylactic acid, but the porous structure may affect the light transmittance of the packaging bag.

[0019] Optionally, the porous silica is pretreated as follows: The porous silica is immersed in a polyglycolic acid solution under negative pressure, filtered and dried to obtain modified porous silica; The modified porous silica is immersed in a blended solution prepared by mixing PMMA emulsion and deionized water in a mass ratio of 1:1, and then filtered and dried after immersion for 3-5 minutes to prepare an intermediate; The intermediate was mixed with trimethoxy (1H, 1H, 2H, 2H-heptadecafluorodecyl) silane and deionized water, and the temperature was raised to 80-90° C. in a sealed environment, and the reaction was carried out for 3-4 hours.

[0020] By adopting the above technical scheme, the porous structure of porous silica will produce light scattering, affecting the transparency of the packaging bag, and the pores of the porous silica are filled with a polyglycolic acid solution with higher light transmittance under negative pressure, thereby improving the transparency of the packaging film, and then optically transparent materials are used to further improve the transparency of the porous silica and improve the hydrophobic properties of the porous silica. Finally, trimethoxy (1H, 1H, 2H, 2H-heptadecafluorodecyl) silane is deposited on the surface of the porous silica by a gas phase method for hydrophobic modification, which effectively reduces the surface energy of the porous silica, thereby improving its hydrophobicity. The surface activity of the hydrophobically modified porous silica is reduced, and it can be better dispersed in the polylactic acid matrix, and the interface compatibility between the two is improved to form a tightly connected whole, which plays a role in stress transmission, thereby improving the mechanical properties of the packaging bag to a certain extent, and can refine the grains, thereby improving the light transmittance of the packaging bag and enhancing the light transmittance of the material.

[0021] Optionally, the density of the polylactic acid is 1.24-1.28 g / cm 3 .

[0022] Optionally, the dispersant is selected from polyethylene glycol or acetyl tributyl citrate, the antioxidant is selected from antioxidant 1010 or antioxidant 168, the flame retardant is ammonium polyphosphate, the lubricant is ethylene bis-12-hydroxystearamide, and the antistatic agent is ester-based quaternary ammonium salt.

[0023] In a second aspect, the present application provides a method for preparing a biodegradable and environmentally friendly electrically insulating plastic packaging bag, using the following technical solution: A method for preparing a degradable and environmentally friendly electrical insulating plastic packaging bag comprises the following steps: The polylactic acid, organic zirconium phosphate, hydrophobically modified cellulose nanocrystals, polyimide / aluminum fluoride composite nanofibers, antistatic agent, dispersant, antioxidant, inorganic filler, lubricant and flame retardant are uniformly mixed, heated to hot melt, cast into film, cut and heat-sealed to make bags, so as to obtain an electrically insulating plastic packaging bag.

[0024] In summary, this application has the following beneficial effects: 1. Since the present application adopts polylactic acid as the base material and incorporates raw materials such as organic zirconium phosphate, hydrophobically modified cellulose nanocrystals and polyimide / aluminum fluoride composite nanofibers, the heat resistance of the packaging bag is effectively improved, making it less likely to produce thermal deformation when used at high temperatures, and reducing the movement of molecules at high temperatures, reducing conductive channels or current leakage, improving the insulation capacity of the packaging bag under high temperature use, and enhancing the tensile strength of the packaging bag.

[0025] 2. In the present application, it is preferred to prepare hydrophobically modified cellulose nanocrystals by grafting octadecylamine with tannic acid and then mixing it with 3-aminopropyltrihydroxysilane-modified boron nitride nanosheets to reduce the movement of molecular chains, enhance the heat resistance and insulation properties of the hydrophobically modified cellulose nanocrystals, and improve their mechanical strength.

[0026] 3. In the present application, polyimide / aluminum fluoride composite nanofibers are prepared by mixing polyamic acid solution and aluminum fluoride and then electrospinning and thermal imidization. Both polyimide and aluminum fluoride have excellent electrical insulation ability and strong heat resistance, which can improve the heat resistance and electrical insulation ability of the packaging bag.

[0027] 4. The present application uses porous silica as a filler, and uses polyglycolic acid solution for impregnation, PMMA emulsion for hydrophobic modification, and trimethoxy (1H, 1H, 2H, 2H-heptadecafluorodecyl) silane vapor deposition to modify the surface of the porous silica, thereby reducing the scattering of light by the porous silica, while increasing the dispersibility and compatibility of the porous silica in polylactic acid, and improving the transparency and mechanical strength of the packaging bag. DETAILED DESCRIPTION

[0028] The following examples further illustrate the present application in detail.

[0029] Preparation Examples 1-6 of Hydrophobically Modified Cellulose Nanocrystals Preparation Example 1: (1) 20 g of cellulose nanocrystals were dispersed in deionized water, and ultrasonically dispersed for 10 min to obtain a cellulose nanocrystal suspension with a concentration of 2 wt%, and the pH was adjusted to 8 with a sodium hydroxide solution, and 4 g of tris (hydroxymethyl) aminomethane (Tris) buffer was added, and 12 g of tannic acid was added, and stirred at room temperature for 24 h to obtain an aqueous dispersion. The cellulose nanocrystals were selected from Zhejiang Jinjiahao Green Nanomaterials, and the product number was CNC; (2) dissolving 20 g of octadecylamine in 1000 ml of anhydrous ethanol, mixing with the aqueous dispersion, stirring at 50° C. for 24 h, centrifuging, collecting the lower layer of precipitate, washing with ethanol, and freeze-drying to obtain pretreated cellulose nanocrystal powder; (3) The pretreated cellulose nanocrystal powder was dispersed in deionized water, ultrasonically dispersed for 2 hours, 3-aminopropyltrihydroxysilane-modified boron nitride nanosheets were added, stirred for 6 hours, vacuum filtered, dried at 130°C, crushed, and ground. The mass ratio of 3-aminopropyltrihydroxysilane-modified boron nitride nanosheets to pretreated cellulose nanocrystal powder was 1:0.1. The preparation method of 3-aminopropyltrihydroxysilane-modified boron nitride nanosheets was as follows: boron nitride powder was dispersed in isopropanol to obtain a solution with a concentration of 4 mg / ml, ultrasonically treated for 7 hours to obtain a suspension, vacuum filtered, washed with ethanol and deionized water, and dried to obtain boron nitride nanosheets. 100 mg of boron nitride nanosheets were dispersed in 100 ml of ethanol, 0.1 ml of 3-aminopropyltrihydroxysilane was added, stirred evenly, stirred at 60°C for 24 hours, vacuum filtered, washed with ethanol and deionized water, and dried.

[0030] Preparation Example 2: (1) 20 g of cellulose nanocrystals were dispersed in deionized water, and ultrasonically dispersed for 10 min to obtain a cellulose nanocrystal suspension with a concentration of 2 wt%, and the pH was adjusted to 9 with a sodium hydroxide solution, and 4 g of tris (hydroxymethyl) aminomethane (Tris) buffer was added, and 8 g of tannic acid was added, and stirred at room temperature for 20 h to obtain an aqueous dispersion. The cellulose nanocrystals were selected from Zhejiang Jinjiahao Green Nanomaterials, and the product number was CNC; (2) dissolving 18 g of octadecylamine in 1000 ml of anhydrous ethanol, mixing with the aqueous dispersion, stirring at 60° C. for 20 h, centrifuging, collecting the lower layer of precipitate, washing with ethanol, and freeze-drying to obtain pretreated cellulose nanocrystal powder; (3) The pretreated cellulose nanocrystal powder was dispersed in deionized water, ultrasonically dispersed for 3 hours, 3-aminopropyltrihydroxysilane-modified boron nitride nanosheets were added, stirred for 8 hours, vacuum filtered, dried at 100°C, crushed, and ground. The mass ratio of 3-aminopropyltrihydroxysilane-modified boron nitride nanosheets to pretreated cellulose nanocrystal powder was 1:0.2. The preparation method of 3-aminopropyltrihydroxysilane-modified boron nitride nanosheets was as follows: boron nitride powder was dispersed in isopropanol to obtain a solution with a concentration of 4 mg / ml, ultrasonically treated for 7 hours to obtain a suspension, vacuum filtered, washed with ethanol and deionized water, and dried to obtain boron nitride nanosheets. 100 mg of boron nitride nanosheets were dispersed in 100 ml of ethanol, 0.1 ml of 3-aminopropyltrihydroxysilane was added, stirred evenly, stirred at 60°C for 24 hours, vacuum filtered, washed with ethanol and deionized water, and dried.

[0031] Preparation Example 3: (1) Disperse 20 g of cellulose nanocrystals in deionized water, ultrasonically disperse for 10 min to obtain a 2 wt% cellulose nanocrystal suspension, adjust the pH to 9 with sodium hydroxide solution, add 4 g of tris(hydroxymethyl)aminomethane (Tris) buffer, add 8 g of tannic acid, stir at room temperature for 20 h to obtain an aqueous dispersion, vacuum filter, and dry to constant weight. The cellulose nanocrystals are selected from Zhejiang Jinjiahao Green Nanomaterials, with the product number CNC.

[0032] Preparation Example 4: (1) Disperse 20 g of cellulose nanocrystals in deionized water and ultrasonically disperse for 10 min to obtain a cellulose nanocrystal suspension with a concentration of 2 wt%. The cellulose nanocrystals are selected from Zhejiang Jinjiahao Green Nanomaterials, with the product number CNC; (2) Dissolve 20 g of octadecylamine in 1000 ml of anhydrous ethanol, mix with the cellulose nanocrystal suspension, stir at 50°C for 24 h, centrifuge, collect the lower precipitate, wash with ethanol, and freeze-dry.

[0033] Preparation Example 5: The difference from Preparation Example 1 is that 3-aminopropyltrihydroxysilane-modified boron nitride nanosheets are not added.

[0034] Preparation Example 6: The difference from Preparation Example 1 is that the boron nitride nanosheets are not modified with 3-aminopropyltrihydroxysilane. Example

[0035] Example 1: A biodegradable and environmentally friendly electrical insulating plastic packaging bag, the raw material dosage is shown in Table 1, wherein the density of polylactic acid is 1.24 g / cm 3, selected from Nature works of the United States, with a brand name of 4032D, the hydrophobically modified cellulose nanocrystals are prepared by Preparation Example 1, the dispersant is polyethylene glycol 6000, the antioxidant is antioxidant 1010, the lubricant is ethylene bis-12-hydroxystearamide, the antistatic agent is an ester-based quaternary ammonium salt, selected from Shandong Henry, with a model of TEP-90, the flame retardant is ammonium polyphosphate, the inorganic filler is porous silica, selected from Foshan Oulite New Materials, with a model of SDK-2480, and a particle size of 2 μm, and the organic zirconium phosphate is prepared by pre-intercalating zirconium phosphate with methylamine and then intercalating with octadecyltrimethylammonium chloride. The specific method is as follows: 5.82 g of zirconium phosphate is dispersed in 300 ml of deionized water, and 12 g of The concentration of 25% methylamine solution was reacted at room temperature for 72 hours, filtered, washed with deionized water for 3 times, and vacuum dried at 90°C for 24 hours to obtain methylamine pre-intercalated zirconium phosphate; the methylamine pre-intercalated zirconium phosphate was prepared into a suspension with a concentration of 5wt% with deionized water, 2.5g of octadecyltrimethylammonium chloride was added, and the mixture was stirred at 70°C for 3 hours and then centrifuged. The precipitate was washed with 50% ethanol solution until there was no chloride ion (tested with 0.1mol / l silver nitrate solution), vacuum dried at 65°C for 24 hours, and ground through a 200-mesh sieve. Polyimide / aluminum fluoride composite nanofibers were prepared by electrospinning a polyamic acid solution and an aluminum fluoride composite and then imidizing the composite. The specific method is as follows: 113.44g A mixture of N, N-dimethylacetamide and tetrahydrofuran was mixed with 0.02 mol of diamine monomer (the molar ratio of 2,2'-dimethylbenzidine and 4,4-diaminodiphenyl ether was 5:5), stirred until completely dissolved, and then 0.02 mol of 3,3',4,4'-biphenyltetracarboxylic dianhydride was added, and refluxed and stirred for 12 hours in an ice water bath and under nitrogen protection to obtain a polyamic acid solution with a concentration of 15 wt%, and a mixture of N, N-dimethylacetamide and tetrahydrofuran was added, and a polyamic acid solution with a concentration of 8 wt% was obtained by dilution, and aluminum fluoride was added. The mass ratio of polyamic acid solution and aluminum fluoride is 1:0.01. Stir for 2 hours, let it stand for defoaming, and obtain spinning solution. After electrospinning, nanofiber matrix is ​​obtained, and then imidization is carried out to obtain composite nanofibers. The spinning voltage is 15 kV, the receiving distance is 20 cm, and the spinning rate is 0.6 ml / h. The imidization process: heat to 150 ° C at a rate of 5 ° C / min in a nitrogen atmosphere, keep warm for 120 minutes, heat to 250 ° C at 4 ° C / min, keep warm for 60 minutes, heat to 370 ° C at 3 ° C / min, and keep warm for 30 minutes.

[0036] The method for preparing the above-mentioned degradable and environmentally friendly electrically insulating plastic packaging bag comprises the following steps: Polylactic acid, organic zirconium phosphate, hydrophobically modified cellulose nanocrystals, polyimide / aluminum fluoride composite nanofibers, antistatic agent, dispersant, antioxidant, inorganic filler, lubricant and flame retardant are mixed evenly, heated to 220°C for hot melting, cast into a film with a thickness of 220 μm, cut, and heat-sealed at 200°C to make bags to obtain electrically insulating plastic packaging bags.

[0037] Table 1 Amount of raw materials used for the degradable and environment-friendly electrical insulating plastic packaging bags in Examples 1-4 Example 2: A degradable and environmentally friendly electrically insulating plastic packaging bag, which is different from the paper clip in Example 1. The raw material dosage is as shown in Table 1, and the hydrophobically modified cellulose nanocrystals are made from Preparation Example 2. The mass ratio of polyamic acid solution and aluminum fluoride in polyimide / aluminum fluoride nanofibers is 1:0.12.

[0038] Example 3-4: A degradable and environmentally friendly electrical insulating plastic packaging bag. The difference from Example 1 is that the amount of raw materials used is as shown in Table 1. Example 5: A degradable and environmentally friendly electrically insulating plastic packaging bag, which is different from Example 1 in that the hydrophobically modified cellulose nanocrystals are made from Preparation Example 3.

[0039] Example 6: A degradable and environmentally friendly electrically insulating plastic packaging bag, which is different from Example 1 in that the hydrophobically modified cellulose nanocrystals are made from Preparation Example 4.

[0040] Example 7: A degradable and environmentally friendly electrically insulating plastic packaging bag, which is different from Example 1 in that the hydrophobically modified cellulose nanocrystals are made from Preparation Example 5.

[0041] Example 8: A degradable and environmentally friendly electrically insulating plastic packaging bag, which is different from Example 1 in that the hydrophobically modified cellulose nanocrystals are made from Preparation Example 6.

[0042] Example 9: A degradable and environmentally friendly electrically insulating plastic packaging bag. The difference from Example 1 is that the organophosphate zirconium is pretreated as follows: the organophosphate zirconium is blended with poloxamer 407 and polycaprolactone in a mass ratio of 0.05:0.04:1, the temperature is raised to 90°C, melted, extruded and granulated. The melt index of polycaprolactone (160°C, 5kg) is 3g / 10min, and the average molecular weight is 80,000g / mol. It is selected from Solvay, USA, model 6800.

[0043] Example 10: A degradable and environmentally friendly electrically insulating plastic packaging bag. The difference from Example 1 is that the organophosphate zirconium is pretreated as follows: the organophosphate zirconium is blended with poloxamer 407 and polycaprolactone in a mass ratio of 0.03:0.02:1, the temperature is raised to 90°C, melted, extruded and granulated. The melt index of polycaprolactone (160°C, 5kg) is 3g / 10min, and the average molecular weight is 80,000g / mol. It is selected from Solvay, USA, model 6800.

[0044] Example 11: A degradable and environmentally friendly electrically insulating plastic packaging bag. The difference from Example 10 is that the organic zirconium phosphate is subjected to the following pretreatment: the organic zirconium phosphate and polycaprolactone are blended in a mass ratio of 0.03:1, the temperature is raised to 90°C, melted, extruded, and granulated. The melt index of polycaprolactone (160°C, 5kg) is 3g / 10min, and the average molecular weight is 80,000g / mol. It is selected from Solvay, USA, model 6800.

[0045] Example 12: A degradable and environmentally friendly electrically insulating plastic packaging bag. The difference from Example 10 is that the organophosphate zirconium is subjected to the following pretreatment: the organophosphate zirconium and poloxamer 407 are blended in a mass ratio of 0.03:0.02, the temperature is raised to 90°C, mixed evenly, and crushed.

[0046] Example 13: A degradable and environmentally friendly electrical insulating plastic packaging bag, which is different from Example 10 in that the porous silica is pretreated as follows: ① The porous silica was immersed in a 15wt% polyglycolic acid solution at a negative pressure of 0.05MPa for 20min, and then the pressure was released, filtered and dried to obtain the modified porous silica. The polyglycolic acid solution was prepared from 15g of polyglycolic acid and a mixture of tetrahydrofuran and N,N-dimethylformamide in a volume ratio of 1:1. The polyglycolic acid was selected from Lanab Pharmaceuticals, Wuhan, China, and the product number was lnb-pga; ② The modified porous silica was immersed in a blended solution of a 26wt% PMMA emulsion (mixed with 26g PMMA and dimethylformamide) and deionized water in a mass ratio of 1:1, and then filtered and dried after immersion for 5 minutes to prepare an intermediate. The PMMA was selected from Chi Mei, Taiwan, China, and the model was CM-211; ③ Mix the intermediate with trimethoxy (1H, 1H, 2H, 2H-heptadecafluorodecyl) silane and deionized water in a mass ratio of 1:0.5:2, heat to 80°C in a sealed environment, and react for 4 hours.

[0047] Example 14: A degradable and environmentally friendly electrically insulating plastic packaging bag. The difference from Example 13 is that the porous silica is not impregnated with the polyglycolic acid solution, but is immersed in the blended liquid for 5 minutes, filtered and dried, and then mixed with trimethoxy (1H, 1H, 2H, 2H-heptadecafluorodecyl) silane and deionized water in a ratio of 1:0.5:2, and reacted at 80°C for 4 hours.

[0048] Example 15: A degradable and environmentally friendly electrically insulating plastic packaging bag. The difference from Example 13 is that the modified porous silica is not impregnated with PMMA emulsion, and the modified porous silica is mixed with trimethoxy (1H, 1H, 2H, 2H-heptadecafluorodecyl) silane and deionized water in a ratio of 1:0.5:2 at 80°C for 4 hours.

[0049] Example 16: A degradable and environmentally friendly electrically insulating plastic packaging bag, which differs from Example 13 in that the intermediate is not mixed with trimethoxy(1H,1H,2H,2H-heptadecafluorodecyl)silane and deionized water in a ratio of 1:0.5:2 at 80°C for 4 hours.

[0050] Comparative Example Comparative Example 1: A degradable and environment-friendly electrically insulating plastic packaging bag, which differs from Example 1 in that no hydrophobically modified cellulose nanocrystals are added.

[0051] Comparative Example 2: A degradable and environment-friendly electrically insulating plastic packaging bag, which differs from Example 1 in that an equal amount of cellulose nanocrystals is used to replace the hydrophobically modified cellulose nanocrystals.

[0052] Comparative Example 3: A degradable and environment-friendly electrically insulating plastic packaging bag, which differs from Example 1 in that no organic zirconium phosphate is added.

[0053] Comparative Example 4: A degradable and environmentally friendly electrically insulating plastic packaging bag, which differs from Example 1 in that no polyimide / aluminum fluoride composite nanofibers are added.

[0054] Performance testing 1. Tensile strength: Tested in accordance with GB / T13022-1991 "Test method for tensile properties of plastic films", with a tensile speed of 5 mm / min and a clamp distance of 50 mm.

[0055] 2. Transmittance: Use a visible light spectrophotometer (Shanghai Youke Instrument, Model 723) to test the transmittance of the packaging bag. The detection wavelength is 600 mm, the scanning speed is 1 nm / min, the interval is set to 10 nm, and air is used as the collection background for the test characterization.

[0056] 3. Initial decomposition temperature: The thermal stability was tested using a German NETZSCH TG-209F3 thermogravimetric analyzer. About 8 mg of each sample was selected and heated from 25°C to 800°C at a heating rate of 10°C / min under nitrogen flow. The initial decomposition temperature of the material during the test was recorded.

[0057] 4. Volume resistivity: Tested at 60°C in accordance with GB / T15662-1995 "Test method for volume resistivity of conductive and antistatic rates".

[0058] 5. Water contact angle: Prepare a sample with a size of 10mm×10mm, use a contact angle meter (OCA20 from Germany) to characterize the hydrophobicity of the packaging bag, use a microscopic pillow to drop water on the packaging bag, the droplet is 3μL of deionized water, measure the water contact angle, test each sample three times, and take the average value.

[0059] 6. Degradation rate: Prepare packaging bag samples with a diameter of 10 cm and a mass of about 1.5 g to ensure that the mass and size of the samples are highly consistent to ensure the comparability of the experiment. Select soil, bury the samples below the soil surface, cover the soil after placing the samples and ensure that the samples are in full contact with the soil. Bury them for a total of 120 days, take out the samples, clean them, dry them in a blast drying oven and weigh them, compare the changes before and after burial through mass measurement, and evaluate the degradation performance of the samples in the soil environment by the mass change rate.

[0060] Table 2 Performance test of biodegradable and environmentally friendly electrical insulating plastic packaging bags Combining Examples 1-4 and the data in Table 2, it can be seen that the packaging bags prepared in Examples 1-4 have a high volume resistivity at 60°C and have very high insulation properties. In addition, the packaging bags have high tensile strength, high light transmittance, strong heat resistance, large contact angle with water, strong hydrophobicity, and are degradable and relatively environmentally friendly.

[0061] In Example 5, the hydrophobically modified cellulose nanocrystals prepared in Preparation Example 3 are used. Compared with Preparation Example 1, Preparation Example 3 uses only tannic acid to coat the cellulose nanocrystals. The surface of the cellulose nanocrystals contains a polytannic acid layer, which affects the compatibility with substrates such as polylactic acid, reduces the tensile strength of the packaging bag, and reduces the light transmittance and water contact angle. Due to the increase in hydrophilicity, the degradation rate of the material increases, but the heat resistance is weakened, and the electrical insulation performance does not change significantly.

[0062] In Example 6, the hydrophobically modified cellulose nanocrystals prepared in Preparation Example 4 were used. Compared with Example 1, only octadecylamine was used to modify the cellulose nanocrystals. It can be seen that the packaging bag has better hydrophobicity, degradability and light transmittance, but the heat resistance is slightly reduced.

[0063] In Example 7, the hydrophobically modified cellulose nanocrystals prepared in Preparation Example 5 were used. Compared with Preparation Example 1, 3-aminopropyltrihydroxysilane-modified boron nitride nanosheets were not added in Preparation Example 5. Compared with Example 1, the packaging bag prepared in Example 7 had increased transparency, accelerated degradation rate, significantly decreased volume resistivity, weakened electrical insulation ability, and weakened tensile strength and heat resistance.

[0064] Compared with Example 1, Example 8 uses the hydrophobically modified cellulose nanocrystals prepared in Preparation Example 6. The data in Table 2 show that the tensile strength of the packaging bag prepared in Example 8 is slightly reduced, the hydrophobicity is weakened, and the light transmittance and heat resistance are reduced.

[0065] Compared with Example 1, Example 9 and Example 10 also used poloxamer 407 and polycaprolactone to pretreat the organophosphate zirconium. Table 2 shows that the volume resistivity of the packaging bags prepared in Example 9 and Example 10 increased, the tensile strength increased, the degradation rate increased, the heat resistance temperature increased, and various properties were improved.

[0066] Compared with Example 10, Example 11 and Example 12 do not use poloxamer 407 and polycaprolactone respectively. It can be seen that the performance of the packaging bags prepared in Example 11 and Example 12 has different changes in heat resistance, degradation ability, tensile strength and other properties.

[0067] Compared with Example 10, Example 13 also uses polyglycolic acid solution, PMMA emulsion, trimethoxy (1H, 1H, 2H, 2H-heptadecafluorodecyl) silane, etc. to perform a series of pretreatments on the porous silica. Table 2 shows that the transparency of the packaging bag prepared in Example 13 is significantly increased, the hydrophobicity is enhanced, the degradation rate is slightly decreased, but still retains a relatively high degradation rate, the tensile strength is increased, the transmittance is increased, the transparency is enhanced, and the heat resistance is increased.

[0068] Compared with Example 13, Example 14 does not immerse the porous silica in the polyglycolic acid solution. The data in Table 2 show that the transparency of the packaging bag prepared in Example 14 is significantly reduced, and the tensile strength is reduced. In Example 15, the modified porous silica is not immersed in PMMA emulsion, and in Example 16, the intermediate is not mixed with trimethoxy (1H, 1H, 2H, 2H-heptadecafluorodecyl) silane, etc. It can be seen that the packaging bags prepared in Examples 15 and 16 have slightly reduced heat resistance, reduced electrical insulation ability, and poor transparency.

[0069] In Comparative Example 1, no hydrophobically modified cellulose nanocrystals were added. The data in Table 2 showed that the heat resistance of the packaging bag was reduced, the tensile strength was weakened, the transparency was reduced, and the electrical insulation was weakened. In Comparative Example 2, cellulose nanocrystals were used instead of hydrophobically modified cellulose nanocrystals, and the tensile strength and other properties of the packaging bag were reduced, but still higher than those in Comparative Example 1.

[0070] Compared with Example 1, Comparative Example 3 does not add organic zirconium phosphate. From the data in Table 2, it can be seen that the packaging bag made in Comparative Example 3 has reduced heat resistance, weakened tensile strength, weakened degradation ability, but slightly increased transparency.

[0071] In Comparative Example 4, no polyimide / aluminum fluoride composite nanofibers were added. Compared with Example 1, the tensile strength thereof decreased, the light transmittance increased, but the heat resistance decreased, and the electrical insulation decreased.

[0072] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A degradable and environmentally friendly electrical insulating plastic packaging bag, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of polylactic acid, 1-4 parts of organic zirconium phosphate, 2-5 parts of hydrophobically modified cellulose nanocrystals, 4-10 parts of polyimide / aluminum fluoride composite nanofibers, 1-3 parts of dispersant, 1-4 parts of antioxidant, 3-5 parts of inorganic filler, 1-3 parts of lubricant, 1-3 parts of antistatic agent and 3-5 parts of flame retardant.

2. The degradable and environmentally friendly electrical insulating plastic packaging bag according to claim 1, characterized in that: The hydrophobically modified cellulose nanocrystals include cellulose nanocrystals, tannic acid and octadecylamine in a mass ratio of 1:0.4-0.6:0.9-1.

3. The degradable and environmentally friendly electrical insulating plastic packaging bag according to claim 2, characterized in that: The preparation method of the hydrophobically modified cellulose nanocrystal is as follows: The pH of the cellulose nanocrystal suspension with a concentration of 2-3 wt% is adjusted to 8-9, Tris buffer and tannic acid are added, and stirred for 20-24 hours to obtain an aqueous dispersion; The anhydrous ethanol solution of octadecylamine is mixed with the aqueous dispersion, stirred at 50-60° C. for 20-24 hours, centrifuged, the precipitate is collected, washed, and freeze-dried to obtain a pretreated cellulose nanocrystal powder; The pretreated cellulose nanocrystal powder is dispersed in deionized water, ultrasonically dispersed for 2-3 hours, 3-aminopropyltrihydroxysilane modified boron nitride nanosheets are added, stirred for 6-8 hours, vacuum filtered, dried at 100-130°C, and ground. The mass ratio of 3-aminopropyltrihydroxysilane modified boron nitride nanosheets to pretreated cellulose nanocrystal powder is 0.1-0.2:

1.

4. The degradable and environmentally friendly electrical insulating plastic packaging bag according to claim 1, characterized in that: The organic zirconium phosphate is pretreated as follows: the organic zirconium phosphate is blended with poloxamer 407 and polycaprolactone in a mass ratio of 0.03-0.05:0.02-0.04:1, followed by granulation.

5. The degradable and environmentally friendly electrical insulating plastic packaging bag according to claim 1, characterized in that: The polyimide / aluminum fluoride composite nanofiber is prepared by electrostatically spinning a polyamic acid solution and an aluminum fluoride composite and then imidizing the composite. The mass ratio of the polyamic acid solution to the aluminum fluoride is 1:0.01-0.

012.

6. The degradable and environmentally friendly electrical insulating plastic packaging bag according to claim 1, characterized in that: The inorganic filler is porous silica.

7. The degradable and environmentally friendly electrical insulating plastic packaging bag according to claim 6, characterized in that: The porous silica is pretreated as follows: The porous silica is immersed in a polyglycolic acid solution under negative pressure, filtered and dried to obtain modified porous silica; The modified porous silica is immersed in a blended solution prepared by mixing PMMA emulsion and deionized water in a mass ratio of 1:1, and then filtered and dried after immersion for 3-5 minutes to prepare an intermediate; The intermediate was mixed with trimethoxy (1H, 1H, 2H, 2H-heptadecafluorodecyl) silane and deionized water, and the temperature was raised to 80-90° C. in a sealed environment, and the reaction was carried out for 3-4 hours.

8. The degradable and environmentally friendly electrical insulating plastic packaging bag according to claim 1, characterized in that: The density of the polylactic acid is 1.24-1.28 g / cm 3 .

9. The degradable and environmentally friendly electrical insulating plastic packaging bag according to claim 1, characterized in that: The dispersant is selected from polyethylene glycol or acetyl tributyl citrate, the antioxidant is selected from antioxidant 1010 or antioxidant 168, the flame retardant is ammonium polyphosphate, the lubricant is ethylene bis-12-hydroxystearamide, and the antistatic agent is ester-based quaternary ammonium salt.

10. The method for preparing the degradable and environment-friendly electrical insulating plastic packaging bag according to any one of claims 1 to 9, characterized in that: The following steps are involved: The polylactic acid, organic zirconium phosphate, hydrophobically modified cellulose nanocrystals, polyimide / aluminum fluoride composite nanofibers, antistatic agent, dispersant, antioxidant, inorganic filler, lubricant and flame retardant are uniformly mixed, heated to hot melt, cast into film, cut and heat-sealed to make bags, so as to obtain an electrically insulating plastic packaging bag.

Citation Information

Patent Citations

  • Secondary modification of layered inorganic substance alpha-zirconium phosphate and preparation method and application thereof

    CN109535481A

  • High-strength low-dielectric polyimide multilayer film and preparation method thereof

    CN112409621A

  • Biodegradable tough composite material and preparation method thereof

    CN115433442A

Cited By

  • Preparation method of high-temperature-resistant degradable plastic and application of high-temperature-resistant degradable plastic in food packaging

    CN120904647A

  • Medicinal chlorinated butyl rubber sealing ring and preparation method thereof

    CN121045697A